2015
DOI: 10.1159/000369715
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-149 Suppresses Colorectal Cancer Cell Migration and Invasion by Directly Targeting Forkhead Box Transcription Factor FOXM1

Abstract: Background/Aims: The aim of this study is to investigate the clinicopathological and prognostic values of miR-149 expression and its roles in colorectal cancer (CRC) progression. Methods: qRT-PCR was performed to detect miR-149 expression in CRC cell lines or tissues. Also, the clinical significance of miR-149 expression was investigated. The study further explored whether miR-149 inhibits migration and invasion of CRC cells by targeting the mammalian Forkhead Box M1 (FOXM1). Results: miR-149 was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 35 publications
3
74
0
Order By: Relevance
“…miRNA is thereby a potential diagnostic and prognostic marker of TSCC with therapeutic potential (18)(19)(20). Previous studies revealed that miR-149 was downregulated in colorectal cancer, breast cancer, gastric cancer, glioma, melanoma and non-small cell lung cancer (21)(22)(23)(24)(25)(26). This study investigated the expression, biological functions and molecular mechanisms of miR-149 in TSCC.…”
Section: Discussionmentioning
confidence: 96%
“…miRNA is thereby a potential diagnostic and prognostic marker of TSCC with therapeutic potential (18)(19)(20). Previous studies revealed that miR-149 was downregulated in colorectal cancer, breast cancer, gastric cancer, glioma, melanoma and non-small cell lung cancer (21)(22)(23)(24)(25)(26). This study investigated the expression, biological functions and molecular mechanisms of miR-149 in TSCC.…”
Section: Discussionmentioning
confidence: 96%
“…MiRNAs can function as an oncogene, and the targeting of tumour suppressor genes by these oncogenic miRNAs provides favourable conditions for tumour growth, metastasis and infiltration [24, 25]. On the other hand, miRNAs can also have tumour-suppressive function, and the targeting of oncogenes by these miRNAs can contribute to tumour apoptosis, differentiation and treatment [26-28]. As a consequence of the important functions mediated by miRNAs in cancer cells, potential therapeutic approaches that target this pathway have recently attracted attention [29-31].…”
Section: Discussionmentioning
confidence: 99%
“…Although traditional surgical resection TME (total mesorectal excision) and CME (complete mesocolic excision) achieve excellent oncological control and long-term survival for colorectal cancer patients, these approaches are also associated with substantial morbidity and mortality [11,12]. …”
Section: Discussionmentioning
confidence: 99%